Short review on domperidone tablet - Sharma, Shaveta; Chandel, Diksha; Sudan, Puneet; Jain, Upendra K. (Creative Pharma Assent, 2017)
Oral route is presently the gold standard in the pharmaceutical industry where it is regarded as the safest, most economical and most convenient method of drug delivery resulting in highest patient compliance. Pediatric and geriatric patients find it difficult to swallow solid dosage forms like tablets. Mouth dissolving tablet that dissolve or disintegrate rapidly in oral cavity result in solution, is an ultimate remedy for this problem in addition they give pleasing mouth feeling. ODT has advantages such as patient compliance, quick onset of action, improved bioavailability. Domperidone tablet (ODT) gives relief from nausea, vomiting. This review gives us all information about pharmacokinetic, pharmacodynamic, uses, precautions, side effects of domperidone tablets